TECHNOLOGICAL BREAKTHROUGH: UZBEKISTAN ON THE WAY TO AN INNOVATIVE FUTURE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The author of this article emphasizes that the development of technology plays a key role in increasing production efficiency, reducing costs and improving product quality. The main aspects discussed in the article include technology transfer, innovative development, increasing efficiency, competitiveness and economic growth. The strategic role of the state in stimulating innovative development and technology transfer was also noted. State programs and initiatives are aimed at introducing innovative technologies in the economic and social spheres of Uzbekistan.